Pemanfaatan Media Flash Card Pada Materi Keragaman Hayati Untuk Meningkatkan Student Agency Siswa - Lestari, Tuti Rina (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to enhance the student agency of 11th-grade social science students at SMA IT As Syifa Boarding School, initially recorded at only 40%, through the use of flash card media. Student agency encompasses the aspects of voice, choice, and ownership. The research employed Classroom Action Research (CAR) with a two-cycle model, consisting of planning, action, observation, and reflection. Data were collected through observations, questionnaires, and documentation, and then analyzed to measure the development of student agency. The results showed a significant increase from 40% in the pre-cycle to 74% in the first cycle and 80% in the second cycle. This improvement was driven by flash cards that encouraged students to interact actively, engage in discussions, and express their opinions during learning activities. Overall, this study demonstrates that flash card media effectively enhances student engagement and fosters their ability to take an active and responsible role in the learning process.